Sosialisasi Pentingnya Lembaga Keuangan Mikro Syariah Bagi Umkm Di Desa Benteng Ciampea Bogor - Azizah Mursyidah; Abdul Khoiri (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2022)
The implementation of community is focused on Benteng Ciampea Village, Bogor. The livelihoods of some residents are farmers, food traders, and entrepreneurs. It is a livelihood that many people are starting to do to increase their income. This paper aims to conduct a study on the existence of Microfinance Institutions (MFIs). Socialization and education about the importance of LKMS in Benteng Village, the Methods of this Reasearch using a qualitative approach with data collection carried out through observation, documentation studies and in-depth interviews. The results of this study indicate that education on the importance of LKMS in Benteng Village is very influential on increasing community capacity, this is evident from community funds that continue to roll through LKMS and increase competence, as well as assistance from related stakeholders.